Molybdenum cofactor and isolated sulphite oxidase deficiencies: Clinical and molecular spectrum among Egyptian patients. (September 2016) - Zaki, Maha S.; Selim, Laila; EL-Bassyouni, Hala T.; Issa, Mahmoud Y.; Mahmoud, Iman; Ismail, Samira; Girgis, Mariane; Sadek, Abdelrahim A.; Gleeson, Joseph G.; Abdel Hamid, Mohamed S.
Abstract: Aim: Molybdenum cofactor deficiency (MoCD) and Sulfite oxidase deficiency (SOD) are rare autosomal recessive conditions of sulfur-containing amino acid metabolism with overlapping clinical features and emerging therapies. The clinical phenotype is indistinguishable and they can only be differentiated biochemically. MOCS1, MOCS2, MOCS3, and GPRN genes contribute to the synthesis of molybdenum cofactor, and SUOX gene encodes sulfite oxidase. The aim of this study was to elucidate the clinical, radiological, biochemical and molecular findings in patients with SOD and MoCD. Methods: Detailed clinical and radiological assessment of 9 cases referred for neonatal encephalopathy with hypotonia, microcephaly, and epilepsy led to a consideration of disorders of sulfur-containing amino acid metabolism. The diagnosis of six with MoCD and three with SOD was confirmed by biochemical tests, targeted sequencing, and whole exome sequencing where suspicion of disease was lower. Results: Novel SUOX mutations were detected in 3 SOD cases and a novel MOCS2 mutation in 1 MoCD case. Most patients presented in the first 3 months of life with intractable tonic–clonic seizures, axial hypotonia, limb hypertonia, exaggerated startle response, feeding difficulties, and progressive cystic encephalomalacia on brain imaging. A single patient with MoCD had hypertrophic cardiomyopathy, hitherto unreported with these diseases. Interpretation: Our results emphasize that intractable neonatal seizures, spasticity, and feeding difficulties can be important early signs for these disorders. Progressive microcephaly, intellectual disability and specific brain imaging findings in the first year were additional diagnostic aids. These clinical cues can be used to minimize delays in diagnosis, especially since promising treatments are emerging for MoCD type A. Highlights: Recommendations to physicians on how to suspect MoCD and SOD in clinical settings. Previously unreported clinical finding in MoCD. Example of benefits of exome sequencing in uncharacteristic presentations of disease. Novel mutations in MOCS2 and SUOX genes. Novel mutation in MOCS2 gene in a patient with uncharacteristic phenotype.